2020
DOI: 10.1371/journal.pone.0236530
|View full text |Cite
|
Sign up to set email alerts
|

Transcription profiles reveal sugar and hormone signaling pathways mediating tree branch architecture in apple (Malus domestica Borkh.) grafted on different rootstocks

Abstract: Apple trees grafted on different rootstock types, including vigorous rootstock (VR), dwarfing interstock (DIR), and dwarfing self-rootstock (DSR), are widely planted in production, but the molecular determinants of tree branch architecture growth regulation induced by rootstocks are still not well known. In this study, the branch growth phenotypes of three combinations of 'Fuji' apple trees grafted on different rootstocks (VR: Malus baccata; DIR: Malus baccata/ T337; DSR: T337) were investigated. The VR trees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
(78 reference statements)
1
3
0
Order By: Relevance
“…Anatomical structure, material transport, photosynthesis, plant hormones, and other factors are closely related to dwarfing rootstocks; however, limited studies have shown the relationships between the degree of dwarfing and metabolomics. Earlier studies have shown that small-molecule organic acids can affect plant growth and development [57]. Compared with vigorous ('Shatangju'/'Shatang Mandarin') graft combination, most of the organic acids in the dwarf ('Shatangju'/'Flying Dragon') graft combination was upregulated, which is consistent with previous research results.…”
Section: Discussionsupporting
confidence: 91%
“…Anatomical structure, material transport, photosynthesis, plant hormones, and other factors are closely related to dwarfing rootstocks; however, limited studies have shown the relationships between the degree of dwarfing and metabolomics. Earlier studies have shown that small-molecule organic acids can affect plant growth and development [57]. Compared with vigorous ('Shatangju'/'Shatang Mandarin') graft combination, most of the organic acids in the dwarf ('Shatangju'/'Flying Dragon') graft combination was upregulated, which is consistent with previous research results.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, overexpression of MdNAC1 gene is associated with dwarfism in transgenic apple by regulating endogenous ABA and BR biosynthesis [ 89 ]. Transcriptomic analysis of apple trees grafted on different rootstocks showed that sugar metabolism-related genes and complex hormone regulatory networks complicated the IAA, CK, ABA, and GA pathways [ 90 ].…”
Section: Effects Of the Rootstock On Different Horticultural Traits I...mentioning
confidence: 99%
“…The heat map and hierarchical clustering of DEGs were generated using TBtools software with FPKM ( Chen et al., 2020a ). Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis of DEGs were based on all expressed background genes and performed using the GOseq R package ( Young et al., 2010 ) and KOBAS software ( Chen et al., 2020b ). GO and KEGG terms with p adj < 0.05 and p < 0.05 were considered significantly enriched by DEGs, respectively.…”
Section: Methodsmentioning
confidence: 99%